PENINGKATAN KETERAMPILAN MENGAJAR GURU MELALUI PENERAPAN SUPERVISI KLINIS DI SD NEGERI 130001 TANJUNGBALAI - Nazrahwati Nazrahwati (Jurnal Guru Kita PGSD, 2020)
Abstract: Improvement of Teacher Teaching Skills through the Implementation of Clinical Supervision in 130001 Tanjungbalai Public Elementary School. The purpose of this study was to determine the improvement in teaching skills of teachers after clinical supervision was applied at 130001 Elementary School Tanjungbalai in the 2018/2019 academic year. This study uses a school action research approach (action research) using a cycle strategy of two cycles. The subjects of this study were 15 teachers at 130001 Tanjungbalai Public Elementary School. The results showed that: 1) the teaching skills of teachers in Cycle I in the aspects of asking questions, providing reinforcement, providing variety, explaining, opening and closing lessons, guiding small group discussions, managing classes, and small group and individual teaching skills, on average in the sufficient category, the second cycle has increased ie in the good category. 2) The application of clinical supervision has been proven to be successful in improving teacher teaching skills with improvements that occur in each aspect and the achievement of indicators of success in every aspect in Cycle II.Keywords: Teaching Skills, Clinical Supervision.Abstrak: Peningkatan Keterampilan Mengajar Guru melalui Penerapan Supervisi Klinis di SD Negeri 130001 Tanjungbalai. Tujuan penelitian ini adalah untuk mengetahui peningkatan keterampilan mengajar guru setelah diterapkan supervisi klinis di SD Negeri 130001 Tanjungbalai tahun pelajaran 2018/2019. Penelitian ini menggunakan pendekatan penelitian tindakan sekolah (action research) dengan menggunakan strategi siklus sebanyak dua siklus. Subyek penelitian ini adalah 15 guru di SD Negeri 130001 Tanjungbalai. Hasil penelitian menunjukkan bahwa: 1) keterampilan mengajar guru pada Siklus I pada aspek keterampilan bertanya, memberikan penguatan, memberikan variasi, menjelaskan, membuka dan menutup pelajaran, membimbing diskusi kelompok kecil, mengelola kelas, dan keterampilan mengajar kelompok kecil dan perorangan, rata-rata dalam kategori cukup, pada siklus II mengalami peningkatan yaitu dalam  kategori baik. 2) Penerapan supervisi klinis terbukti berhasil meningkatkan keterampilan mengajar guru dengan peningkatan yang terjadi pada masnig-masing aspek dan ketercapaian indikator keberhasilan setiap aspek pada Siklus II.Kata Kunci: Keterampilan Mengajar, Supervisi Klinis.